Legal Perception of the Community Regarding Productive Zakat and Its Utilization In Makassar - Zainuddin Zainuddin; Hasbuddin Khalid (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
Zakat is one of the pillars of Islam that must be fulfilled by all Muslims. Zakat in its implementation, must be determined and regulated by religion and the state. This study aims (1) To find out and analyze the legal perceptions of mustahiq (zakat receiver) regarding productive zakat in Makassar; and (2) to find out and analyze the legal perception of mustahiq regarding the productive utilization zakat in Makassar. This research is based on legal research conducted with an empirical juridical approach, which sees the law not only as a set of normative norms or what becomes the text of the law but also looks at how the law interacts with the community (law in action). This research will be conducted in Makassar. In this study, the analysis used qualitative analysis and quantitative analysis was carried out based on primary data regarding the opinions of informants in the frequency distribution. The results achieved in this study are Makassar community perceives that productive zakat is the same position as consumptive zakat which is spent on household needs. Mustahiq provided revolving funds through qardhul hasan loans more to spend for household needs or consumer goods so that it does not provide benefits as a productive business. Zakat funds in the form of qardhul hasan loans provided by the Baznas Makassar should be used for productive ventures. Besides, the people of Makassar community still perceive that the funds lent from the Baznas Makassar do not need to be returned because they consider that the funds are their rights as poor people and their use is for consumptive purposes and there is no obligation to return the zakat funds. Funding loans under the qardhul hasan scheme managed by Baznas Makassar are revolving and rotating in nature